2018
DOI: 10.1186/s12944-018-0872-8
|View full text |Cite
|
Sign up to set email alerts
|

Profile of cardiac lipid metabolism in STZ-induced diabetic mice

Abstract: BackgroundLipotoxicity contributes to diabetic myocardial disease. In this study, we investigated the lipid species contributing to lipotoxicity and the relationship with peroxisomal β-oxidation in the heart of diabetic mice.MethodsMale C57BL/6 mice were randomly divided into a Diabetic group (intraperitoneal injection of STZ) and a Control group (saline). Cardiac function indexes [ejection fraction (EF%) and fractional shortening (FS%)] were evaluated by echocardiography. Morphological changes in the myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…Insulin deficiency decreases glucose delivery in cardiomyocytes and use of fatty acids as an alternative energy source. This elevation increases subsequent triglyceride synthesis in the heart leading to cellular lipotoxicity and the beginning of cardiac dysfunction [20]. In accordance with these reports, in the present study, hyperlipidemia characterized by increased levels of cholesterol, triglycerides, LDL and VLDL were observed in untreated diabetic animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Insulin deficiency decreases glucose delivery in cardiomyocytes and use of fatty acids as an alternative energy source. This elevation increases subsequent triglyceride synthesis in the heart leading to cellular lipotoxicity and the beginning of cardiac dysfunction [20]. In accordance with these reports, in the present study, hyperlipidemia characterized by increased levels of cholesterol, triglycerides, LDL and VLDL were observed in untreated diabetic animals.…”
Section: Discussionsupporting
confidence: 92%
“…In diabetic state, due to decrease in glucose uptake by cardiac cells, the fatty acid is used as a fuel [20]. The oxidation of this causes increase in lipid levels which are also observed in the current study.…”
Section: Effect On Lipid Profile In Stz Induced Dcmsupporting
confidence: 80%
“…Phosphocholine is attributed to toxic lipid species, and was found to be higher in diabetic mice. 34 It is normal that phosphocholine serum levels are higher in these patients. Formate is associated with vitamin B12 metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…In these untreated patients, higher serum methionine levels may indicate a worsened physiological state of MetS. Phosphocholine is attributed to toxic lipid species, and was found to be higher in diabetic mice 34 . It is normal that phosphocholine serum levels are higher in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it is known that 3-ketoacyl-CoA thiolase abolishes BNIP3-mediated apoptosis and mitochondrial damage [83]. It was shown that 3-ketoacyl-CoA thiolase increased in the heart of STZ-induced diabetic mice [84]. The -3.4-fold decrease in the disulfide-isomerase protein level may also contribute to the suppression of apoptosis (Table 5) [85].…”
Section: Resultsmentioning
confidence: 99%